2005
DOI: 10.1016/j.jasms.2005.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Peptide Ion Fragmentation Induced by Vacuum Ultraviolet Light

Abstract: One Hundred Fifty-Seven nm photodissociation of singly protonated peptides generates unusual distributions of fragment ions. When the charge is localized at the C-terminus of the peptide, spectra are dominated by x-, v-, and w-type fragments. When it is sequestered at the N-terminus, a-and d-type ions are overwhelmingly abundant. Evidence is presented suggesting that the fragmentation occurs via photolytic radical cleavage of the peptide backbone at the bond between the ␣-and carbonyl-carbons followed by radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
183
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(208 citation statements)
references
References 63 publications
22
183
2
1
Order By: Relevance
“…In this report, we specifically focus on photofragmentation results that are different from those obtained with CID experiments. As we reported in our earlier 157 nm photofragmentation experiments, with the current experimental configuration precursor depletion rates of ϳ25% have been obtained [22,23]. In some cases, dozens of different fragment ions form from a single precursor, and this significantly limits the intensity of each one.…”
Section: Resultssupporting
confidence: 55%
“…In this report, we specifically focus on photofragmentation results that are different from those obtained with CID experiments. As we reported in our earlier 157 nm photofragmentation experiments, with the current experimental configuration precursor depletion rates of ϳ25% have been obtained [22,23]. In some cases, dozens of different fragment ions form from a single precursor, and this significantly limits the intensity of each one.…”
Section: Resultssupporting
confidence: 55%
“…Previously we have demonstrated that 157 nm photodissociation of singly-charged peptide ions yields abundant a ϩ 1 radical ions [38,39]. In the present work, these odd-electron radical ions were isolated in an ion trap mass spectrometer to study their structure and fragmentation behavior.…”
Section: Resultsmentioning
confidence: 90%
“…For small model peptide ions, investigations beyond simple mechanistic interpretation have been reported, such as the quantum chemical search for reaction paths [8 -10]. However, there has not been much study on kinetics of peptide ion dissociation [11].Tandem mass spectral patterns for protonated peptides are affected by factors, such as the charge state, the number of arginine residue, and the energy regime [2,3,12,13]. For singly protonated peptides-these will be called peptide ions from now on-without an arginine residue, b and y types (see reference [2] for product ion symbols) are the major product ions regardless of the energy regime.…”
mentioning
confidence: 99%
“…For peptide ions with an arginine residue, b/y channels (rearrangement) are dominant in the lowenergy regime [3], such as in low-energy collisionally activated dissociation (CAD) and post-source decay (PSD). In the high-energy regime, such as in highenergy CAD [2] and ultraviolet photodissociation (UV-PD) [12][13][14], however, a new set of homolytic C ␣ -CO cleavage channels become dominant, even though the rearrangement channels still operate.Statistical theory of mass spectra (Rice-RamspergerKassel-Marcus theory, RRKM) [15] is known to provide an excellent description for the dissociation of small polyatomic ions. There have been some debates on whether RRKM would be valid for dissociation of large biomolecules [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation